Association of national COVID-19 cases with objectively and subjectively measured mental health proxies in the Austrian Football league – an epidemiological study. Issue 1 (1st January 2021) - van der Zee-Neuen, Antje; Seymer, Alexander; Schaffler-Schaden, Dagmar; Herfert, Jürgen; ÓBrien, James; Johansson, Tim; Kutschar, Patrick; Ludwig, Stephan; Stöggl, Thomas; Keeley, David; Flamm, Maria; Osterbrink, Jürgen
Abstract : We aimed to explore the association of national COVID-19 data with the objective and subjective mental health proxies (i.e. location variance, self-reported sleep quality, level of recovery, perceived risk of infection) in team and staff members of five professional Austrian Football clubs. Data were conveniently collected during the implementation of a novel monitoring concept. The concept was designed to enable safe continuation of professional Football during the COVID-19 pandemic. These data were matched with Austrian COVID-19 data and smartphone collected location data. Multivariable linear regression models explored the association of COVID-19, defined as daily novel or active Austrian cases of COVID-19, with the mental health proxies. An increasing number of novel Austrian COVID-19 cases was significantly associated with deteriorating sleep quality (B 0.48, 95% CI 0.05; 1.00). An increasing number of active Austrian COVID-19 cases was significantly associated with an increase in perceived infection risk (B 0.04, 95% CI 0.00; 0.07) and location variance (B 0.28, 95% CI 0.06; 0.49). An increasing Austrian COVID-19 incidence is adversely associated with mental health in professional Footballers and staff members. During the ongoing pandemic, targeted mental care should be included in the daily routines of this population.